The influence of blood glucose level on tear break up time among young adults with diabetes - Rahman, Aziimah; Mat Noh, Nor Ain; Badarudin, Noor Ezailina; Che Azemin, Mohd Zulfaezal; Hamirudin, Aliza Haslinda (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2018)
Background: It has been reported that diabetics are more likely to develop tear film dysfunction compared to non-diabetics. Even so, there has been very little research reported on the correlation between blood glucose level and quality of tears. Objective: The purpose of the study was to investigate the influence of blood glucose level on TBUT among young adults with diabetes in Malaysia. Methods: A cross-sectional study consisting of 37 diabetic patients within the age range of 19-39 years was carried out at IIUM Optometry Clinic, IIUM Kuantan. The subjects were tested for random blood glucose level (RBS) and undergone tear break up time (TBUT) test. Nonparametric test was used namely Spearman correlation to determine the association between RBS and TBUT. Results: TBUT median (interquartile range) value was 7.5 (11.55) seconds. Meanwhile, correlation analysis revealed negative correlation between random blood glucose (RBS) and TBUT in diabetics (r = -0.126). However, this correlation is not statistically significant (p>0.05). Conclusion: Tear film break up time were not significantly associated with the random blood glucose level. Tear film break up time seems to not be affected by blood glucose level.